PENGARUH STRATEGI POINT COUNTER POINT TERHADAP KETERAMPILAN BERBICARA DALAM PEMBELAJARAN TEMATIK - ROKHIMAWAN, MOHAMAD AGUNG; LELI, NUR (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2018)
The thematic learning model applied in MI Al-Iman Tambakrejo Sleman is a learning that brings together one lesson with another lesson, learner-centered learning. The problem found in MI Al-Iman is the lack of speaking skills of students in expressing their opinions or responding or responding when learning takes place. The purpose of this study was to determine the influence and how much the contribution of the Counter Point Point strategy to the speaking skills of class V students at MI Al-Iman Tambakrejo Sleman. Problems in students' speaking skills occur in fifth grade students at MI Al-Iman Tambakrejo Sleman, namely that the low speaking skills of students, most students are not brave and shy to speak in public. In addition they have difficulty issuing an idea or ideas during learning. The population in this study was MI Al-Iman Tambakrejo Sleman and the sample used was the fifth grade students with 16 students. The research used a quantitative approach. Data collection methods used are interviews, observations, questionnaires and documentation. Data analysis techniques using product moment correlation and simple regression. Based on the results of the analysis of the data obtained by the significant value is 0.032, which means smaller than 0.05, this study has an effect between the Point Counter Point strategy of speaking skills, the results of the determination index (R2) which is the amount of contribution to the influence of Counter Point Point strategy variables on skills speaking is 28.9% of speaking skills. So the Point Counter Point strategy has a contribution of influence on speaking skills of 28.9%.